Neuroprotective potential of GDF11 in experimental intracerebral hemorrhage in elderly rats. (May 2019) - Anqi, Xiao; Ruiqi, Chen; Yanming, Ren; Chao, You
Highlights: Neurological impairment after elderly ICH could be attenuated by GDF11. The mechanism for antioxidant effect of GDF11 in post-ICH is proposed. The mechanism for mitochondrial protective effect of GDF11 after ICH is proposed. Abstract: The occurrence of intracerebral hemorrhage (ICH) costs long-standing neurologic deficits in ICH survivors, elderly ones in particular. Recent researches have proved rejuvenating effect of Growth Differentiation Factor 11 (GDF11) in improving multiple systemic diseases on old individuals. Thus, we designed this study to explore the neuroprotective effect and mechanisms of GDF11 in elderly ICH. 45 aged male Sprague-Dawley (SD) rats were randomly divided into sham + vehicle, ICH + vehicle and ICH + rGDF11 groups. ICH models were induced via injection of autologous whole blood into right basal ganglia of rats. ICH rats were given a daily injection of either recombinant (r) GDF11 at 0.1 mg/kg or vehicle for 28 days prior to operation and continued till the experiment completed. Neurological deficits, brain edema, cell apoptosis, microglial activation and heme oxygenase-1 (HO-1) positive cells were compared among each group. In addition, cytochrome c release, mitochondrial calcium buffering capacity and ATP level were monitored to explore the level of mitochondrial injury. Seen in the result, behavior disorders, severe perihematomal edema, inflammation, apoptosis, oxidative stress and mitochondria damage indicated a significant increase in ICH + vehicle group. While in ICH + rGDF11 group, administration of rGDF11 successfully reduced neurological deficits and alleviated ICH-induced edema, inflammation, apoptosis, oxidative stress, and mitochondria damage in perihematomal tissues. Collectively, our study showed that GDF11 ameliorated ICH-induced neurological deficits in elderly individuals via reducing perihematomal edema, apoptosis, inflammatory reaction, oxidative stress and improving mitochondrial dysfunction, indicating neuroprotective effect of GDF11 in elderly ICH.